Rapid Eye Movement Sleep Deprivation Produces Long-Term Detrimental Effects in Spatial Memory and Modifies the Cellular Composition of the Subgranular Zone - Soto-Rodriguez, Sofia; Lopez-Armas, Gabriela; Luquin, Sonia; Ramos-Zuñiga, Rodrigo; Jauregui-Huerta, Fernando; Gonzalez-Perez, Oscar; Gonzalez-Castañeda, Rocio E. (Frontiers in Cellular Neuroscience, 2016)
Sleep deprivation (SD) affects spatial memory and proliferation in the dentate gyrus. It is unknown whether these deleterious effects persist in the long run. The aim of this study was to evaluate the proliferation, differentiation and maturation of neural progenitors as well as spatial memory 21 days after suffering sleep deprivation. Sixty-day old male Balb/C mice were exposed to 72-h REM-SD. Spatial memory, cell fate, apoptosis and expression levels of insulin-like growth factor 1 receptor (IGF-1R) were evaluated in the hippocampus at 0, 14 and 21 days after SD or control conditions. After 21-d recovery period, memory performance was assessed with the Barnes maze, we found a significant memory impairment in SD mice vs. control (94.0 ± 10.2s vs. 25.2 ± 4.5s; p < 0.001). The number of BrdU+ cells was significantly decreased in the SD groups at day 14 (controls = 1.6 ± 0.1 vs. SD mice = 1.2 ± 0.1 cells/field; p=0.001) and at day 21 (controls = 0.2 ± 0.03 vs. SD mice = 0.1 ± 0.02 cells/field; p < 0.001). A statistically significant decrease was observed in neuronal differentiation (1.4 ± 0.1 cells/field vs. 0.9 ± 0.1 cells/field, p = 0.003). Apoptosis was significantly increased at day 14 after SD (0.53 ± 0.06 TUNEL+ cells/field) compared to controls (0.19 ± 0.03 TUNEL+ cells/field p<0.001) and at 21-d after SD (SD mice 0.53±0.15 TUNEL+ cells/field; p = 0.035). At day 0, IGF-1R expression showed a statistically significant reduction in SD animals (64.6 ± 12.2 units) when compared to the control group (102.0 ± 9.8 units; p = 0.043). However, no statistically significant differences were found at day 14 and 21 after SD. In conclusion, a single exposition to SD for 72-h can induce deleterious effects that persist for at least three weeks. These changes are characterized by spatial memory impairment, reduction in the number of hippocampal BrdU+ cells and persistent apoptosis rate. In contrast, changes IGF-1R expression appears to be a transient event.